A Framework for Sharing Heterogeneous Grid Resources in a Campus Environment - Ma, T; Xiong, X; Wallom, D (2015)
Grid computing enables the access of heterogeneous computational resources across a dynamic set of physical organisations seamlessly. A campus grid is an example of the grid solution which is located within a single administrative domain. In the majority of installations these enable connection of all institutionally owned computational resources, making them transparently available to appropriately registered members of staff. In this paper we introduce the design and implementation of a lightweight campus grid framework. It manages a set of heterogeneous computational resources, using virtual organisation based policies for each individual grid resource and enables user's to transparently access resources through a unified user-friendly interface. The proposed framework can discover, aggregate and broker all of these heterogeneous resources with low management costs that matches users' requirements. With this framework, a campus grid enables university-wide, regional-wide, national and international grid resources become transparently available to university members through their university account without knowing how to access each individual resource. Such a framework allows scalable grid resource sharing, virtual organisation based resource management, dynamical and autonomous resource brokering with improved usability and manageability in a campus grid environment